IP subnetting for beginners : your complete guide to master IP bubnetting in 4 simple steps - Nastase, Ramon ([United States] : Ramon Nastase, 2021)
If you want to know everything about IP Subnetting and how the Internet works, then this book is definitely for you. It doesn't matter if you are studying for the CCNA exam or you are just trying to master all kinds of networking techniques. The book is designed for everyone looking to start learning Networking. You don't have to be tech-savvy to understand what's being explained in the chapters of this book. The content is suitable for both beginners and those who are more knowledgeable on the subject. You won't have to learn all sorts of complicated terminology to understand the content of this book. The steps to IP Subnetting are simple and easy to apply.
1. What is IP ? -- 2. The Structure of an IPv4 Packet -- 3. IP Subnetting -- 4. Configuring an IP address on windows 7/8/10 -- 5. Configuring an IP address on the Router.
Keywords: NETWORKING; COMPUTER NETWORKS PROTOCOL